Treatment for COVID-19 patients in Vietnam: Analysis of time-to-recovery - Khuong Quynh Long; Hoang Hong Hanh; Tran Thi Tuyet Hanh; La Ngoc Quang; Hoang Van Minh (Asian Pacific Journal of Tropical Medicine, 2020)
Objective: To describe the recovery time and related factors among COVID-19 patients in Vietnam. Methods: We used the secondary data obtained from the official database of the Ministry of Health of Vietnam and other public data sources that were available by April 9th, 2020. Cox proportional hazards model was carried out to identify factors related to recovery time among COVID-19 patients. Results: By April 9th, 2020, the cumulative number of COVID-19 cases detected in Vietnam was 255, of which 129 (50.6%) patients had fully recovered. The median recovery time of patients was 17 (95% CI=16-19) days. Older patients had a lower likelihood of recovery (HR=0.98, 95% CI=0.97-0.99, P<0.001), whereas patients with a history of international incoming travel had a higher likelihood of recovery (HR=1.57, 95% CI=1.03-2.40, P=0.036). There was no statistically significant difference in the recovery time of patients treated in different hospital settings. Conclusions: More attention is needed for older patients and who did not have international travel history. Patients confirmed with COVID-19 could be treated at local health facilities to avoid unnecessary referrals and burdens to specialized hospitals at the central level.